Comprehensive phenomic and genomic studies of the species, Pectobacterium cacticida and proposal for reclassification as Alcorniella cacticida comb. nov - Jonca, Joanna; Pirhonen, Minna; Waleron, Michal Mateusz; Gawor, Jan; Mrozik, Agnieszka; Smoktunowicz, Magdalena; Waleron, Krzysztof; Waleron, Malgorzata (Frontiers in Plant Science, 2024)
Introduction Pectobacterium cacticida was identified as the causative agent of soft rot disease in cacti. Due to a high potential of spread in the face of global warming, the species poses a significant threat to horticultural and crop industry. The aim of this study was to revise the genomic, physiology and virulence characteristics of P. cacticida and update its phylogenetic position within the Pectobacterium genus. Methods Whole genome sequences of five P. cacticida strains were obtained and subjected to comprehensive genomic and phylogenomic data analyses. We assessed the presence of virulence determinants and genes associated with host and environmental adaptation. Lipidomic analysis, as well as biochemical and phenotypic assays were performed to correlate genomic findings. Results Phylogenomic analysis revealed that P. cacticida forms a distinct lineage within the Pectobacterium genus. Genomic evaluation uncovered 516 unique proteins, most of which were involved in cellular metabolism. They included genes of carbohydrate metabolism and transport and ABC transporters. The main differing characteristics from other Pectobacterium species were the lack of a myo-inositol degradation pathway and the presence of the malonate decarboxylase gene. All tested strains were pathogenic towards Opuntia spp., chicory, Chinese cabbage, and potato, but exhibited only mild pathogenicity towards carrot. Discussion This study sheds light into the genomic characteristics of P. cacticida and highlights the pathogenic potential of the species. Unique genes found in P. cacticida genomes possibly enhance the species’ survival and virulence. Based on phylogenomic analyses, we propose the reclassification of P. cacticida to a new genus, Alcorniella comb. nov.